Selective binding of actinomycin D and distamycin A to DNA. - Wilkins, R J (1982)
The exact sites at which a number of drugs inhibit the nick translation of DNA by E.coli DNA polymerase-I have been pinpointed. In order to do this, a method has been developed for sequencing double-stranded plasmid DNA from the site of a specifically induced nick. The initial experiments have concentrated on analysis of drug inhibition of nick translation in a 200 nucleotide region near the Eco Rl origin of pBR313. Many drugs were found to inhibit nick translation in a highly sequence specific manner. For actinomycin D, significant inhibition occurred at just four sites in the nucleotide sequence under test and only one sequence (pGpCpGpCpGpGp) gave really strong inhibition. Distamycin A gave a different pattern of inhibition with particularly strong stops in just two of the many A-T rich regions in the DNA. Experiments with caffeine suggest that factors in addition to primary sequence are important in determining where major inhibition occurs.